Tibetan sheep grazing modifies rodent density and their interactions effect on GHG emissions of alpine meadow - Wang, Yingxin (Sci Rep, 2019)
Digging and mound-building by rodents lead to considerable disturbances in the topsoil and may affect plant composition, soil properties. However, little is known about the effects of these activities on GHG emissions, especially under different grazing management. This paper aimed to measure changes in CO(2) and CH(4) efflux with varying grazing management during the warm and cold seasons and to relate CO(2) and CH(4) efflux to pika burrow density and zokor mound density with different grazing management. Results of this study showed that CO(2) efflux was significantly affected by the grazing season, whereas CH(4) efflux was significantly affected by the grazing system. There were significant relationships between GHG efflux and rodent population density which were regulated by grazing management. CO(2) efflux increased linearly with rodent density under seasonal continuous grazing in warm season. CO(2) and CH(4) efflux and rodent population density showed a significant quadratic convex relationship under rotational grazing at 24 SM/ha in warm and cold seasons and rotational grazing at 48 SM/ha in cold season. Under rotational grazing at light stocking rate (24 SM/ha), appropriate populations of rodents were beneficial for decreasing GHG emissions. This results also used to help drive a best-practices model for grazing practices of local herders.